Service Quality of Jogorogo Community Health Center, Ngawi, Indonesia - Subagyo Subagyo (Humanistic Network for Science and Technology (HNST), 2017)
Community health centers are expected to be able to provide quality health services that meet the needs of the community. Thus, community health centers need to improve services in order to be able to compete, develop, and grow. This survey research describe the satisfaction of the community as customers for services provided by Jogorogo Community Health Center, Ngawi Regency, Indonesia. The population were all people who used health services at the Jogorogo Community Health Center in 2016. The samples were community that utilized health services at the Jogorogo Community Health Center in 2016, selected by quota sampling technique. Each service unit were a patient registration center, general clinic, dental clinic, MCH clinic, medicine room, and inpatient room, each given a quota of 20 customers, while specifically for community health centers assistants were quota of 10 customers, with consideration that the average customer visit at a community health center assistant is lower. The variable was the level of satisfaction with health services provided by community health centers. Data was collected through filling out questionnaires, then analyzed descriptively and presented in the form of spiderweb diagram. Keywords: Community health center, Service quality